(untitled) (REMUNOM, 2025)
This article discusses Afro hair as an important element in the construction of Black identity and belonging, as well as how it can be incorporated into educational settings. The goal is to foster dialogue around Afro hair in pedagogical practices and to propose actions aligned with Law No. 10.639/03, which aims to ensure the teaching of African and Afro-Brazilian history and culture in schools. The school environment often reinforces Eurocentric standards, devaluing Black aesthetics. Making educational spaces inclusive is essential for Black and mixed-race students to feel represented and safe to express their identity. The methodology used was a qualitative study with university students, through an online questionnaire with open-ended questions and participant observation around an expository banner. Most participants recognize hair as an element of identity, resistance, and self-esteem, although many report internal conflicts caused by society’s imposed beauty standards. These findings highlight the urgent need for pedagogical actions that celebrate Black aesthetics.